Graphene reinforced polyacrylonitrile-based carbon fiber and preparation method thereof

By soaking multiple graphene oxide dispersions on polyacrylonitrile-based carbon fibers and processing at high temperatures, the problems of complex preparation and poor performance of graphene-enhanced polyacrylonitrile-based carbon fibers in the prior art are solved, and the mechanical properties and thermal conductivity are significantly improved.

CN119615611APending Publication Date: 2025-03-14BEIJING GRAPHENE RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411944406.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, the preparation method of using graphene to reinforce polyacrylonitrile-based carbon fibers is relatively complex, and graphene oxide is prone to agglomeration or precipitation in solution, affecting the quality and performance of the fibers. At the same time, improving the elastic modulus and thermal conductivity of carbon fibers requires high-temperature graphitization, resulting in a shortening of the fiber life.

Method used

By adding a metal salt solution to the negatively charged graphene oxide dispersion, a positively charged graphene oxide dispersion is prepared, and the acidified polyacrylonitrile fibers are soaked multiple times in the positively charged and negatively charged graphene oxide dispersion, thereby enhancing the interaction force between graphene oxide and fiber. The pre-oxidation, carbonization and graphitization were then performed to obtain graphene-reinforced polyacrylonitrile-based carbon fibers.

Benefits of technology

The uniform adhesion of graphene to the polyacrylonitrile-based carbon fiber surface is achieved, which enhances the mechanical and thermal conductivity of the fiber, simplifies the process flow and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615611A_ABST
    Figure CN119615611A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene reinforced polyacrylonitrile-based carbon fiber and a preparation method thereof. The preparation method comprises the following steps: adding a metal salt solution into a graphene oxide dispersion liquid with negative charges to prepare a graphene oxide dispersion liquid with positive charges; the preparation method comprises the following steps: soaking polyacrylonitrile fibers in a strong acid solution with oxidability for acidizing to obtain acidized polyacrylonitrile fibers; the acidified polyacrylonitrile fiber is soaked in the graphene oxide dispersion liquid with the positive charges, and drying is conducted after soaking is finished; then soaking in the graphene oxide dispersion liquid, and drying after soaking is finished; and sequentially carrying out pre-oxidation, carbonization and graphitization treatment on the polyacrylonitrile fiber coated with the graphene oxide to obtain the graphene reinforced polyacrylonitrile-based carbon fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of carbon fiber preparation, and specifically relates to a graphene-reinforced polyacrylonitrile-based carbon fiber and a preparation method thereof. Background Art

[0002] Carbon fiber is an anisotropic, low-density material with large design freedom, good deep processing performance, and excellent vibration reduction performance. It also has the advantages of excellent vibration attenuation, small thermal expansion coefficient, strong adaptability to sudden environmental changes, and good electrical and thermal conductivity. Therefore, it is used in various fields. Carbon fiber can be divided into three types according to its raw materials: polyacrylonitrile-based, asphalt-based and viscose-based. Among them, polyacrylonitrile-based carbon fiber has become the main component of carbon fiber because its raw materials are easy to obtain and the fiber has excellent comprehensive mechanical properties.

[0003] Polyacrylonitrile is a fiber made by spinning a polymer with acrylonitrile as the main chain structural unit. Carbon fibers prepared with polyacrylonitrile precursor as the precursor have good comprehensive performance and high yield. Polyacrylonitrile-based carbon fibers have high mechanical strength, high modulus, and chemical resistance. Their excellent performance and unique functions have broad application prospects in aerospace, machinery manufacturing, chemical industry, electronic communications, medical equipment and other fields. Graphene has excellent thermal conductivity. The use of graphene and polymer composites to prepare composite materials or fibers can significantly improve the performance of materials, such as mechanical properties and thermal conductivity. However, existing data show that a lot of efforts have been made in using graphene to enhance the performance of polymers, but there are few methods and processes for preparing graphene-enhanced polyacrylonitrile-based carbon fibers.

[0004] At present, the method of compounding graphene with carbon fiber generally adopts chemical vapor deposition or electrostatic spinning. Chemical vapor deposition is to grow graphene on the surface of carbon fiber, so as to achieve close combination between carbon fiber and graphene. Electrostatic spinning is to gradually add graphene oxide dispersion to polyacrylonitrile solution to form a mixed solution containing graphene oxide and polyacrylonitrile. The mixed solution is injected into the electrostatic spinning equipment, and the polymer molecules in the solution are transformed from liquid to fiber form at the spinning nozzle under the action of high electric field. The fiber obtained by spinning is subjected to subsequent heat treatment to obtain graphene composite fiber.

[0005] Growing graphene oxide on the surface of carbon fiber using methods such as CVD usually requires a complex preparation process. This includes pre-treating the surface of the carbon fiber to ensure that the graphene oxide has good contact and compatibility with the carbon fiber; when selecting the growth conditions of graphene oxide, it is necessary to consider parameters such as atmosphere and temperature and make precise adjustments to ensure the uniform growth of graphene oxide; in addition, the thermal stability and surface morphology of the carbon fiber need to be fully considered to avoid uneven growth of graphene oxide on its surface. All these factors together increase the complexity and cost of the preparation process and make process control more difficult.

[0006] Although electrospinning is a relatively simple preparation method, in actual operation, it is necessary to control parameters such as solution concentration, flow rate, and electrostatic field strength to ensure the uniformity and stability of the fiber, so the operation is still somewhat complex. The uniform dispersion of graphene oxide in polyacrylonitrile solution is the key to the success of electrospinning, but due to the properties of graphene oxide, it is easy to agglomerate or precipitate in the solution, resulting in poor dispersion, thus affecting the quality and performance of the fiber. And because the interaction between graphene oxide and polyacrylonitrile is not strong, the fiber structure may be unstable and prone to breakage or shedding, which reduces the mechanical properties and service life of the fiber.

[0007] In the prior art, if the elastic modulus and thermal conductivity of carbon fiber are to be further improved, the carbon fiber needs to be graphitized at 2000°C to 3000°C to obtain graphite fiber with a carbon mass fraction of more than 99%. The elastic modulus of carbon fiber can be greatly improved after high-temperature graphitization treatment. However, as the graphitization temperature increases, the life of the fiber is sharply shortened. How to improve the mechanical properties and thermal conductivity of carbon fiber while retaining its original properties and not converting it into graphite fiber is an urgent problem to be solved. Summary of the invention

[0008] In order to solve the above problems, the present invention provides a method for preparing graphene-reinforced polyacrylonitrile-based carbon fibers with good mechanical properties and thermal conductivity, comprising the following steps:

[0009] (1) adding a metal salt solution to a graphene oxide dispersion with a negative charge to prepare a graphene oxide dispersion with a positive charge;

[0010] (2) soaking the polyacrylonitrile fiber in a strong acid solution having oxidative properties for acidification treatment to obtain acidified polyacrylonitrile fiber;

[0011] (3) soaking the acidified polyacrylonitrile fiber in the graphene oxide dispersion with a positive charge, and drying after soaking; then soaking the acidified polyacrylonitrile fiber in the graphene oxide dispersion with a negative charge, and drying after soaking;

[0012] (4) Pre-oxidation, carbonization, and graphitization are performed on the polyacrylonitrile fiber coated with graphene oxide treated in step (3) to obtain the graphene-reinforced polyacrylonitrile-based carbon fiber.

[0013] According to a specific embodiment of the present invention, the metal salt solution is selected from one or more of an aluminum salt solution, a potassium salt solution, and a sodium salt solution.

[0014] According to a specific embodiment of the present invention, the metal salt solution is selected from aluminum chloride solution.

[0015] According to a specific embodiment of the present invention, in the step (1), the content of the metal salt in the positively charged graphene oxide dispersion is 0.5 wt%-5 wt%.

[0016] According to a specific embodiment of the present invention, the strong acid is sulfuric acid. Preferably, the concentration of the sulfuric acid is in the range of 5wt%-98wt%.

[0017] According to a specific embodiment of the present invention, in step (2), the soaking time is 30 minutes to 24 hours.

[0018] According to a specific embodiment of the present invention, in step (3), the acidified polyacrylonitrile fiber is immersed in the positively charged graphene oxide dispersion for 1 hour to 4 hours; and immersed in the negatively charged graphene oxide dispersion for 1 hour to 4 hours.

[0019] According to a specific embodiment of the present invention, the operation of step (3) is repeated 1-4 times.

[0020] According to a specific embodiment of the present invention, in step (4), the pre-oxidation operation includes: heating at a temperature of 200° C.-300° C. for 0.5 h-3 h under air conditions.

[0021] According to a specific embodiment of the present invention, in step (4), the carbonization operation includes: heating the pre-oxidized fiber at a temperature of 1000° C.-1500° C. for 0.5 h-2 h in a nitrogen atmosphere.

[0022] According to a specific embodiment of the present invention, in the step (4), the graphitization temperature is 2000°C-3000°C, preferably 2800°C-3000°C.

[0023] Another object of the present invention is to provide graphene-reinforced polyacrylonitrile-based carbon fibers prepared by the above-mentioned preparation method.

[0024] Beneficial effects:

[0025] (1) The present invention pre-treats graphene oxide and polyacrylonitrile fiber and adjusts the process flow so that graphene oxide is uniformly attached to the surface of polyacrylonitrile-based carbon fiber, thereby enhancing the interaction force between graphene oxide and polyacrylonitrile-based carbon fiber. At the same time, the high thermal conductivity of graphene oxide is fully utilized to enhance the thermal conductivity of polyacrylonitrile-based carbon fiber. The high thermal conductivity of graphene can improve the thermal treatment performance of carbon / carbon composite materials, making them more suitable for applications in high heat load environments. Therefore, the present invention is committed to providing a carbon / carbon composite material of graphene-reinforced polyacrylonitrile-based carbon fiber with a simpler and more stable process flow.

[0026] (2) Compared with polyacrylonitrile fibers, the graphene-reinforced polyacrylonitrile-based fibers in the present invention have more excellent thermal conductivity, making the heat conduction of the overall composite structure more efficient under high heat load environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the preparation process of the graphene-reinforced polyacrylonitrile-based carbon fiber of the present invention.

[0028] Figure 2 SEM images of raw polyacrylonitrile fiber (a), carbonized fiber (b), and graphitized fiber (c). DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with specific implementation modes.

[0030] The present invention provides a method for preparing graphene-reinforced polyacrylonitrile-based carbon fibers having good mechanical properties and thermal conductivity. Figure 1 , including the following steps:

[0031] (1) adding a metal salt solution to a graphene oxide dispersion with a negative charge to prepare a graphene oxide dispersion with a positive charge; preferably, the metal salt solution is selected from one or more of an aluminum salt solution, a potassium salt solution, and a sodium salt solution; more preferably, the metal salt solution is selected from an aluminum chloride solution;

[0032] (2) soaking the polyacrylonitrile fiber in a strong acid solution having oxidative properties for acidification treatment to obtain acidified polyacrylonitrile fiber;

[0033] (3) soaking the acidified polyacrylonitrile fiber in the graphene oxide dispersion with a positive charge, and drying after soaking; then soaking the acidified polyacrylonitrile fiber in the graphene oxide dispersion with a negative charge, and drying after soaking;

[0034] (4) Pre-oxidation, carbonization, and graphitization are performed on the polyacrylonitrile fiber coated with graphene oxide treated in step (3) to obtain the graphene-reinforced polyacrylonitrile-based carbon fiber.

[0035] The graphene oxide dispersion is a negatively charged solution, into which a metal salt (preferably aluminum chloride) is added to prepare a positively charged graphene oxide dispersion; the positively charged graphene oxide dispersion and the negatively charged graphene oxide dispersion are sequentially coated on polyacrylonitrile fibers, so that the graphene oxide can be fully attached to the fibers, and the positive and negative charges attract each other, so that the graphene oxide is more firmly combined with the fibers, which helps to enhance the interaction between the graphene oxide and the polyacrylonitrile-based carbon fibers, and improves the mechanical properties and thermal conductivity of the obtained product, the graphene-reinforced polyacrylonitrile-based carbon fibers.

[0036] The polyacrylonitrile fiber is acidified in a strong oxidizing acid to oxidize the fiber surface through the strong oxidizing effect of the strong acid, and introduce functional groups such as hydroxyl and carboxyl groups on the fiber surface, which helps to enhance the interaction between graphene oxide and polyacrylonitrile-based carbon fiber, and helps to improve the mechanical properties and thermal conductivity of the resulting product, graphene-enhanced polyacrylonitrile-based carbon fiber.

[0037] A graphene oxide dispersion was chosen as the base material, which can be prepared under laboratory conditions.

[0038] By making our own graphene oxide dispersion in the laboratory, we can flexibly control the quality and structure of the material to ensure it has excellent thermal conductivity.

[0039] Polyacrylonitrile fiber is selected as the raw material of carbon fiber, and the polyacrylonitrile fiber is pretreated in the laboratory to ensure excellent interface bonding between it and graphene oxide.

[0040] In an optional embodiment, the preparation method of the negatively charged graphene oxide dispersion includes: adding graphene oxide to deionized water, stirring for 0.5h-1.5h at a rate of 2000r / min~2200r / min in a high-speed disperser to obtain graphene oxide slurry, wherein the solid content of the graphene oxide slurry ranges from 0.5wt% to 5wt%; homogenizing the graphene oxide slurry 1-5 times at a homogenization pressure of 60MPa-160MPa; vacuum degassing the homogenized graphene oxide slurry for 5min~10min to obtain the negatively charged graphene oxide dispersion.

[0041] In an optional embodiment, in the step (1), the content of the metal salt in the positively charged graphene oxide dispersion is 0.5 wt%-5 wt%.

[0042] The positively charged graphene oxide dispersion prepared by controlling the content of the metal salt within the above range is conducive to its coating on the surface of the acidified polyacrylonitrile fiber, and the mechanical properties and thermal conductivity of the prepared graphene-reinforced polyacrylonitrile-based carbon fiber are better.

[0043] In an optional embodiment, the step (1) specifically comprises: adding a metal salt solution to the graphene oxide dispersion, and stirring at 200 r / min to 2200 r / min for 30 min to 60 min in a high-speed disperser.

[0044] In the technical solution of the present invention, the "strong oxidizing acid" can be a strong oxidizing acid commonly used in the art, such as sulfuric acid, nitric acid, etc.; preferably, the strong acid is sulfuric acid, and more preferably, the concentration range of the sulfuric acid is 5wt%-98wt%.

[0045] In an optional embodiment, in the step (2), the soaking time is 30 minutes to 24 hours.

[0046] In an optional embodiment, in the step (3), the acidified polyacrylonitrile fiber is immersed in the positively charged graphene oxide dispersion for 1-4 hours; and immersed in the negatively charged graphene oxide dispersion for 1-4 hours.

[0047] In an optional embodiment, the operation of step (3) is repeated 1-4 times.

[0048] In the technical solution of the present invention, step (3) is repeated in order to allow the graphene dispersion to fully adhere to the surface of the fiber.

[0049] In an optional embodiment, in the step (4), the pre-oxidation operation includes: heating at a temperature of 200° C. to 300° C. for 0.5 h to 3 h under air conditions.

[0050] In an optional embodiment, in the step (4), the carbonization operation includes: heating the pre-oxidized fiber at a temperature of 1000° C. to 1500° C. for 0.5 h to 2 h under a nitrogen atmosphere.

[0051] In an optional embodiment, in the step (4), the graphitization temperature is 2000°C-3000°C, preferably 2800°C-3000°C.

[0052] Another object of the present invention is to provide graphene-reinforced polyacrylonitrile-based carbon fibers prepared by the above-mentioned preparation method.

[0053] Example 1

[0054] (1) Preparation of a positively charged graphene oxide dispersion: adding graphene oxide to deionized water, stirring at a high-speed disperser at a rate of 2000 r / min for 1 h to obtain a graphene oxide slurry (the solid content of the graphene oxide slurry is in the range of 3 wt%); homogenizing the graphene oxide slurry for 3 times at a homogenization pressure of 160 MPa; vacuum degassing the homogenized graphene oxide slurry for 10 min to obtain a negatively charged graphene oxide dispersion; adding 5 ml of aluminum chloride solution to the negatively charged graphene oxide dispersion, stirring at a high-speed disperser stirring rate of 2000 r / min for 60 min to obtain a positively charged graphene oxide dispersion, wherein the content of aluminum chloride is 3 wt%.

[0055] (2) Preparation of acidified polyacrylonitrile fiber: The polyacrylonitrile fiber was soaked in 30 wt % sulfuric acid for 12 h. After soaking, the polyacrylonitrile fiber was washed with water until neutrality and dried to obtain the acidified polyacrylonitrile fiber.

[0056] (3) Coating polyacrylonitrile fiber with graphene oxide dispersion: The acidified polyacrylonitrile fiber is immersed in a graphene oxide dispersion with a positive charge for 4 hours. After immersion, the fiber is dried. After drying, the fiber is immersed in a graphene oxide dispersion with a negative charge for 4 hours. After immersion, the fiber is dried. Repeat the above steps 3 times.

[0057] (4) Pre-oxidation: The graphene oxide-coated polyacrylonitrile fibers were heated at 240 °C for 1 h under air conditions.

[0058] (5) Carbonization: The pre-oxidized fiber was heated at 1000 °C in a nitrogen atmosphere for 1 h.

[0059] (6) Graphitization: The carbonized fibers are graphitized at 3000°C to obtain graphene-reinforced polyacrylonitrile-based carbon fibers.

[0060] Figure 2 SEM images of raw polyacrylonitrile fiber (a), carbonized fiber (b), and graphitized fiber (c).

[0061] Example 2

[0062] (1) Preparation of a positively charged graphene oxide dispersion: adding graphene oxide to deionized water, stirring at a high-speed disperser at a rate of 2000 r / min for 1 h to obtain a graphene oxide slurry (the solid content of the graphene oxide slurry is in the range of 2 wt%); homogenizing the graphene oxide slurry for 3 times at a homogenization pressure of 160 MPa; vacuum degassing the homogenized graphene oxide slurry for 10 min to obtain a negatively charged graphene oxide dispersion; adding 5 ml of aluminum chloride solution to the negatively charged graphene oxide dispersion, stirring at a high-speed disperser stirring rate of 2000 r / min for 60 min to obtain a positively charged graphene oxide dispersion, wherein the content of aluminum chloride is 3 wt%.

[0063] (2) Preparation of acidified polyacrylonitrile fiber: The polyacrylonitrile fiber was soaked in 30 wt % sulfuric acid for 6 h. After soaking, the polyacrylonitrile fiber was washed with water until neutrality and dried to obtain the acidified polyacrylonitrile fiber.

[0064] (3) Coating polyacrylonitrile fiber with graphene oxide dispersion: The acidified polyacrylonitrile fiber is immersed in a graphene oxide dispersion with a positive charge for 4 hours. After immersion, the fiber is dried. After drying, the fiber is immersed in a graphene oxide dispersion with a negative charge for 4 hours. After immersion, the fiber is dried. Repeat the above steps 4 times.

[0065] (4) Pre-oxidation: The graphene oxide-coated polyacrylonitrile fibers were heated at 240 °C for 1 h under air conditions.

[0066] (5) Carbonization: The pre-oxidized fiber was heated at 1000 °C in a nitrogen atmosphere for 1 h.

[0067] (6) Graphitization: The carbonized fibers are graphitized at 3000°C to obtain graphene-reinforced polyacrylonitrile-based carbon fibers.

[0068] Comparative Example 1

[0069] (1) Preparation of a positively charged graphene oxide dispersion: adding graphene oxide to deionized water, stirring at a high-speed disperser at a rate of 2000 r / min for 1 h to obtain a graphene oxide slurry (the solid content of the graphene oxide slurry is in the range of 3 wt%); homogenizing the graphene oxide slurry for 3 times at a homogenization pressure of 160 MPa; vacuum degassing the homogenized graphene oxide slurry for 10 min to obtain a negatively charged graphene oxide dispersion; adding 5 ml of aluminum chloride solution to the negatively charged graphene oxide dispersion, stirring at a high-speed disperser stirring rate of 2000 r / min for 60 min to obtain a positively charged graphene oxide dispersion, wherein the content of aluminum chloride is 3 wt%.

[0070] (2) Preparation of acidified polyacrylonitrile fiber: The polyacrylonitrile fiber was soaked in 30 wt % sulfuric acid for 12 h. After soaking, the polyacrylonitrile fiber was washed with water until neutrality and dried to obtain the acidified polyacrylonitrile fiber.

[0071] (3) Coating polyacrylonitrile fiber with graphene oxide dispersion: The acidified polyacrylonitrile fiber is immersed in a positively charged graphene oxide dispersion for 4 hours, and then the fiber is dried; the above steps are repeated 3 times.

[0072] (4) Pre-oxidation: The graphene oxide-coated polyacrylonitrile fibers were heated at 240 °C for 1 h under air conditions.

[0073] (5) Carbonization: The pre-oxidized fiber was heated at 1000 °C in a nitrogen atmosphere for 1 h.

[0074] (6) Graphitization: The carbonized fibers are graphitized at 3000°C to obtain graphene-reinforced polyacrylonitrile-based carbon fibers.

[0075] Comparative Example 2

[0076] (1) Preparation of a negatively charged graphene oxide dispersion: Graphene oxide was added to deionized water and stirred at a rate of 2000 r / min in a high-speed disperser for 1 h to obtain a graphene oxide slurry (the solid content of the graphene oxide slurry was 3 wt%); the graphene oxide slurry was homogenized for 3 times at a homogenization pressure of 160 MPa; the homogenized graphene oxide slurry was vacuum degassed for 10 min to obtain a negatively charged graphene oxide dispersion.

[0077] (2) Preparation of acidified polyacrylonitrile fiber: The polyacrylonitrile fiber was soaked in 30 wt % sulfuric acid for 12 h. After soaking, the polyacrylonitrile fiber was washed with water until neutrality and dried to obtain the acidified polyacrylonitrile fiber.

[0078] (3) Coating polyacrylonitrile fiber with graphene oxide dispersion: The acidified polyacrylonitrile fiber is immersed in the negatively charged graphene oxide dispersion for 4 hours, and then the fiber is dried; the above steps are repeated 3 times.

[0079] (4) Pre-oxidation: The graphene oxide-coated polyacrylonitrile fibers were heated at 240 °C for 1 h under air conditions.

[0080] (5) Carbonization: The pre-oxidized fiber was heated at 1000 °C in a nitrogen atmosphere for 1 h.

[0081] (6) Graphitization: The carbonized fibers are graphitized at 3000°C to obtain graphene-reinforced polyacrylonitrile-based carbon fibers.

[0082] Comparative Example 3

[0083] (1) Preparation of a positively charged graphene oxide dispersion: adding graphene oxide to deionized water, stirring at a high-speed disperser at a rate of 2000 r / min for 1 h to obtain a graphene oxide slurry (the solid content of the graphene oxide slurry is in the range of 3 wt%); homogenizing the graphene oxide slurry for 3 times at a homogenization pressure of 160 MPa; vacuum degassing the homogenized graphene oxide slurry for 10 min to obtain a negatively charged graphene oxide dispersion; adding 5 ml of aluminum chloride solution to the negatively charged graphene oxide dispersion, stirring at a high-speed disperser stirring rate of 2000 r / min for 60 min to obtain a positively charged graphene oxide dispersion, wherein the content of aluminum chloride is 3 wt%.

[0084] (2) Coating polyacrylonitrile fiber with graphene oxide dispersion: Soak the polyacrylonitrile fiber in a graphene oxide dispersion with a positive charge for 4 hours, dry the fiber after soaking, soak the fiber in a graphene oxide dispersion with a negative charge for 4 hours, dry the fiber after soaking; repeat the above steps 3 times.

[0085] (3) Pre-oxidation: The graphene oxide-coated polyacrylonitrile fibers were heated at 240 °C for 1 h under air conditions.

[0086] (4) Carbonization: The pre-oxidized fiber was heated at 1000 °C in a nitrogen atmosphere for 1 h.

[0087] (5) Graphitization: The carbonized fibers are graphitized at 3000°C to obtain graphene-reinforced polyacrylonitrile-based carbon fibers.

[0088] The thermal diffusion coefficient of the graphene-reinforced polyacrylonitrile-based carbon fibers prepared in Example 1, Example 2 and Comparative Examples 1-3 was tested using a flash thermal conductivity tester, and the tensile strength of the fibers was tested by a tensile test. The results are shown in Table 1.

[0089] Table 1

[0090]

[0091] It can be seen from the data in Table 1 that, by the method of the present invention, a graphene-reinforced polyacrylonitrile-based carbon fiber product with improved mechanical properties and thermal conductivity (compared to the raw material polyacrylonitrile fiber) is prepared.

[0092] It can be seen from the data of Example 1 and Comparative Examples 1-2 that the technical solution of sequentially coating a positively charged graphene oxide dispersion and a negatively charged graphene oxide dispersion on the surface of the polyacrylonitrile fiber in the present invention is more conducive to improving the mechanical properties and thermal conductivity of graphene reinforced polyacrylonitrile-based carbon fibers compared to the method of only coating a positively charged graphene oxide dispersion or only coating a negatively charged graphene oxide dispersion.

[0093] It can be seen from the data of Example 1 and Comparative Example 3 that the present invention helps to improve the mechanical properties and thermal conductivity of graphene-reinforced polyacrylonitrile-based carbon fibers by acidifying the raw polyacrylonitrile fibers in a strong oxidizing acid and further coating the surface of the raw polyacrylonitrile fibers with a graphene oxide dispersion.

[0094] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.

[0095] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.

Claims

1. A method for preparing graphene-reinforced polyacrylonitrile-based carbon fiber, characterized in that: The following steps are involved: (1) adding a metal salt solution to a graphene oxide dispersion with a negative charge to prepare a graphene oxide dispersion with a positive charge; (2) soaking the polyacrylonitrile fiber in a strong acid solution having oxidative properties for acidification treatment to obtain acidified polyacrylonitrile fiber; (3) soaking the acidified polyacrylonitrile fiber in the graphene oxide dispersion with a positive charge, and drying after soaking; then soaking the acidified polyacrylonitrile fiber in the graphene oxide dispersion with a negative charge, and drying after soaking; (4) Pre-oxidation, carbonization, and graphitization are performed on the polyacrylonitrile fiber coated with graphene oxide treated in step (3) to obtain the graphene-reinforced polyacrylonitrile-based carbon fiber.

2. The preparation method according to claim 1, characterized in that: The metal salt solution is selected from one or more of an aluminum salt solution, a potassium salt solution, and a sodium salt solution.

3. The preparation method according to claim 2, characterized in that: The metal salt solution is selected from aluminum chloride solution.

4. The preparation method according to claim 1, characterized in that: In step (1), the content of the metal salt in the positively charged graphene oxide dispersion is 0.5 wt%-5 wt%.

5. The preparation method according to claim 1, characterized in that: The strong acid is sulfuric acid.

6. The preparation method according to claim 1, characterized in that: In step (2), the soaking time is 30 minutes to 24 hours.

7. The preparation method according to claim 1, characterized in that: In step (3), the acidified polyacrylonitrile fiber is immersed in the graphene oxide dispersion with a positive charge for 1 hour to 4 hours; and immersed in the graphene oxide dispersion with a negative charge for 1 hour to 4 hours.

8. The preparation method according to claim 1, characterized in that: Repeat step (3) 1-4 times.

9. The preparation method according to claim 1, characterized in that: In step (4), the pre-oxidation operation includes: heating at a temperature of 200° C. to 300° C. for 0.5 h to 3 h under air conditions.

10. The preparation method according to claim 1, characterized in that: In step (4), the carbonization operation includes: heating the pre-oxidized fiber at a temperature of 1000° C. to 1500° C. for 0.5 h to 2 h in a nitrogen atmosphere.

11. The preparation method according to claim 1, characterized in that: In step (4), the graphitization temperature is 2000°C-3000°C.

12. A graphene-reinforced polyacrylonitrile-based carbon fiber, characterized in that: The preparation method is described in any one of claims 1 to 11.

Citation Information

Patent Citations

  • Preparation method for flexible and highly-conductive composite carbon fiber cloth

    CN104882613A

  • Preparation method of conductive fibers

    CN106637913A

  • Tungsten selenide / graphene / carbon nanofiber composite material and preparing method thereof

    CN107190361A

  • Preparation method of graphene coating conductive fiber

    CN108774879A